Patient Views for Self-Referral to Specialists - SA Rasoulynejad (Tehran University of Medical Sciences, 2007)
Background: Except in emergency cases, all patients should be seen first by a primary healthcare physician who decides whether a referral to secondary care is necessary. The present study examined the reasons for patient self-referral to specialists. Methods: A random sample of 1036 individuals was selected from people attending public outpatient clinics and specialists' offices in the private health sector. Of the sample, 40% were insured by the closed loop referral; 14% by the semi-closed-loop referral; and 46% were open referral. The data were analysed using χ 2 statistical test. Results: Of the closed-loop referral system patients, 6.8% were self-referred, as were 29.7% of semi-closed referral system patients and 75.5% of open referral system patients. There was a significant association between insurance type and patient self-referral to specialty care (χ 2 = 504; P< 0.0001). The main reasons patients gave for by-passing GPs and self-referring to specialists were: the specialist's high degree of skill in the specific area of the health problem (54%); waste of time to see the GP for a referral (14.9%). Conclusion: The findings of this study demonstrate the high degree of difference in the rates of referral by GP and self-referral according to the healthcare delivery system.